2003
DOI: 10.1074/jbc.m304392200
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the Yeast Phox Homology (PX) Domain Protein Grd19p Complexed to Phosphatidylinositol-3-phosphate

Abstract: Phosphatidylinositol (PI)1 and its phosphorylated derivatives regulate many biological processes, including cell proliferation, cell survival, differentiation, signal transduction, cytoskeleton organization, and membrane trafficking (reviewed in Ref. 1). Various chemical species can be generated by single, double, or triple phosphorylations at the inositol hydroxy groups at positions 3, 4, and 5. Their synthesis and cellular concentrations are regulated by specific lipid kinases and phosphatases. One of the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
85
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(88 citation statements)
references
References 36 publications
3
85
0
Order By: Relevance
“…For example, a recent NMR study on the PX domain of Vam7p revealed that residues in its putative membrane binding loops underwent large changes in chemical shift when dodecylphosphocholine micelles were added to the PX domain-PtdIns3P complex (35). Also, crystal structures of the Grd19p PX domain in the absence and presence of a bound PtdIns3P showed conformational differences in the putative membrane attachment loop (46). This, in conjunction with the PI3K-C2␣ PX domain structure showing high flexibility of the PP II /␣2 loop, suggests that PtdIns(4,5)P 2 binding may also induce the conformational change and thereby facilitate the membrane penetration of hydrophobic side chains.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, a recent NMR study on the PX domain of Vam7p revealed that residues in its putative membrane binding loops underwent large changes in chemical shift when dodecylphosphocholine micelles were added to the PX domain-PtdIns3P complex (35). Also, crystal structures of the Grd19p PX domain in the absence and presence of a bound PtdIns3P showed conformational differences in the putative membrane attachment loop (46). This, in conjunction with the PI3K-C2␣ PX domain structure showing high flexibility of the PP II /␣2 loop, suggests that PtdIns(4,5)P 2 binding may also induce the conformational change and thereby facilitate the membrane penetration of hydrophobic side chains.…”
Section: Discussionmentioning
confidence: 99%
“…PX domains are similar to PH domains in that they have highly variable PI specificities and affinities. High resolution structures of several PX domains that bind the 3Ј-phosphate have been determined as either free proteins or complexes with PI (43)(44)(45)(46). However, the structural information for the PX domains that specifically bind non-3Ј-phosphate-PI has not been available.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(11) The sequence of 1OCU and SNX10 PX were realigned with other sequences that belong to the PX-only subfamily using ClustalW. Models of PX wild-type and mutants were predicted using the program Modeller (ver 9.10).…”
Section: In Silico Studiesmentioning
confidence: 99%